Survey of Mycobacterium avium subspecies paratuberculosis in road-killed wild carnivores in Portugal - Matos, A.C. (2016)
A survey to determine the occurrence of Mycobacterium avium subsp. paratuberculosis (MAP) in wild carnivores in Portugal was conducted by testing samples from road-killed animals between 2009 and 2012. Postmortem examinations were performed and tissues were collected from wild carnivores representing four families and six different species, with a total of 74 animals analyzed. Cultures were performed by using Löwenstein-Jensen and Middlebrook 7H11 solid media and acid-fast isolates were identified by polymerase chain reaction (PCR) and mycobactin dependency characteristics. Tissues were also screened for MAP by directly extracting DNA and testing for the MAP-specific sequences. The occurrence of infected animals (an animal had at least one tissue that was positive for culture or direct PCR) was 27.0% (n = 20). MAP was isolated from culture of 25 tissue samples (3.8%) and was detected by direct PCR in 40 (6.0%) samples. Infection was recorded in 5/6 studied species: 7/49 (14.3%) red foxes (Vulpes vulpes), 3/3 (100%) beech martens (Martes foina), 2/4 (50.0%) Eurasian otters (Lutra lutra), 7/15 (46.7%) Egyptian mongooses (Herpestes ichneumon), and 1/1 (100%) European badger (Meles meles). These species represent three different taxonomic families: Canidae (14.3% were positive), Mustelidae (75.0% were positive), and Herpestidae (46.7% were positive). The results of this study confirm the presence of MAP infection in wild carnivores in Portugal.